Constitutional provisions regarding the judicial control exercised upon the administrative acts issued / adopted in exceptional situations - Coman, Dumitru Ştefan (International Journal of Legal and Social Order, 2023)
Conditions of admissibility of an action in administrative Litigation having as object the administrative acts issued/adopted in exceptional situations, we find them regulated in the Law no. 554/2004 of the administrative Litigation, while in other works we cand find analyzed these problems under the form of the administrative Litigation, on the basis of the Law no. 554/2004, and on the basis of the constitution which is completed with the provisions of the special legislation appliable to the special situations. In the specialty doctrine are identified, as rule, the following conditions of admissibility of an action in the administrative Litigation: the condition that the attacked act to be an administrative act; the condition that that act to affects a right recognized by law or a legitimate interest; the condition that the issued act to emanate from a public authority; the condition of the fulfillment the preliminary administrative procedure; the condition that the action to be introduced within a certain term. In the light of these reasons detached form the constant jurisprudence of the Court from Strasbourg, the Romanian Constitutional Court ruled in the sense that providing a right of effective access to justice, it has to be analyzed also by considering the effects that a judicial decision has upon the right of the person who addressed the justice.